Increased apoptosis in differentiating p27-deficient mouse embryonic stem cells - Bryja, V; Pacherník, J; Soucek, K; Horvath, V; Dvorák, P; Hampl, A (Cellular and molecular life sciences, 2004)
In mouse embryonic stem (mES) cells, the expression of p27 is elevated when differentiation is induced. Using mES cells lacking p27 we tested the importance of p27 for the regulation of three critical cellular processes: proliferation, differentiation, and apoptosis. Although cell cycle distribution, DNA synthesis, and the activity of key G1/S-regulating cyclin-dependent kinases remained unaltered in p27-deficient ES cells during retinoic acid-induced differentiation, the amounts of cyclin D2 and D3 in such cells were much lower compared with normal mES cells. The onset of differentiation induces apoptosis in p27-deficient cells, the extent of which can be reduced by artificially increasing the level of cyclin D3. We suggest that the role of p27 in at least some differentiation pathways of mES cells is to prevent apoptosis, and that it is not involved in slowing cell cycle progression. We also propose that the pro-survival function of p27 is realized via regulation of metabolism of D-type cyclin(s).
Keywords: buněčné dělení; Animals; cykliny; apoptóza; Stem Cells; Cyclins; Embryo, Mammalian; Tretinoin; Apoptosis; Mice, Knockout; nádorové supresorové proteiny; cyklin D2; tretinoin; myši knockoutované; Cyclin-Dependent Kinase Inhibitor p27; buněčná diferenciace; Mice; Cyclin D2; kmenové buňky; interfáze; myši; Interphase; Cyclin D3; Cell Cycle Proteins; Tumor Suppressor Proteins; inhibitor p27 cyklin-dependentní kinasy; Cell Differentiation; zvířata; cyklin D3; proteiny buněčného cyklu; Cell Division; embryo savčí